The concise encyclopaedia of Islam - Glassé, Cyril (Stacey International, 1989)
This volume encompasses the beliefs, practices, history and culture of the Islamic world. Entries cover subjects including all aspects of religious belief, ritual practices, prayer, seers, spiritual and political leaders, art, architecture, sects, laws, social institutions, history, ethnography, nations, languages, science and major cities, and centres of learning. It aims to provide a source and background for understanding of current events in the Islamic world and the complex past.